A simple and efficient strategy to produce transgene-free gene edited plants in one generation using paraquat resistant 1 as a selection marker - Kong, Xiangjiu; Pan, Wenbo; Zhang, Tingyu; Liu, Lijing; Zhang, Huawei (Frontiers in Plant Science, 2023)
DNA integration is a key factor limiting the marketing of CRISPR/Cas9-mediated gene edited crops. Several strategies have been established to obtain transgene-free gene edited plants; however, these strategies are usually time-consuming, technically difficult, providing low mutagenesis efficiency, and/or including a narrow host range. To overcome such issues, we established a paraquat resistant 1 (PAR1)-based positive screening (PARS) strategy, which achieved efficient screening of transgene-free gene edited plants. With PARS, the screening efficiency of mutant increased by 2.81-fold on average, and approximately 10% of T1 plants selected via PARS were transgene-free. Moreover, heritable transgene-free mutations at target loci were identified in the T1 generation. Based on the previous reports and our data, we know that paraquat is toxic to all green plants, PAR1 is conserved among all plant species tested, and the transient expression of Cas9 editor can produce transgene-free gene edited plants. Thus, we assume that the PARS strategy established here has the potential to be widely used to screen transgene-free mutants in various crops using diverse CRISPR/Cas9 delivery approaches.